Analisis Teologi Pendidikan Agama Kristen Berdasarkan Kitab Filemon - Arozatulo Telaumbanua (Jurnal Teologi Berita Hidup, 2020)
Abstract: The Theology of Christian Religious Education in the Book of Philemon teaches about true love, forgiveness and brotherhood. The Book of Philemon contains an educational element that teaches us about effective, creative teaching in educating students. The attitude of educators like the Apostle Paul did is effective teaching to change the attitudes and behavior of students. Partnership is a good collaboration between one another. In collaboration education is very important for the success of learning. This collaboration can take place between students and students, teacher and teacher and teacher and student, so as to create a good learning. In writing this scientific work the writer uses the method of analysis, namely the method of literature that traces and exegetes the book. The success of learning is supported by good and effective learning methods and, above all, is the work of the Holy Spirit.Abstrak: Teologi Pendidikan Agama Kristen dalam Kitab Filemon mengajarkan tentang kasih, pengampunan dan persaudaraan yang sejati. Kitab Filemon mengandung unsur pendidikan yang mengajarkan kita tentang pengajaran yang efektif, kreatif dalam mendidik murid. Sikap pendidik seperti yang Rasul Paulus lakukan merupakan pengajaran yang efektif untuk mengubah sikap dan perilaku para murid. Kemitraan merupakan kerjasama yang baik antara satu dengan yang lain. Di dalam pendidikan kerjasama sangat penting untuk kesuksesan pembelajaran. Kerjasama ini dapat berlangsung antara murid dengan murid, guru dengan guru dan guru dengan siswa, sehingga tercipta satu pembelajaran yang baik. Dalam penulisan karya ilmiah ini penulis menggunakan metode analisis, yaitu metode perspustakaan yang menelusuri dan mengeksegesis kitab. Berhasilnya pembelajaran didukung oleh metode pembelajaran yang baik dan efektif dan yang paling utama merupakan pekerjaan Roh Kudus.